Temporal variation of wheat productivity in relation to temperature in semi arid regions of Gujarat - Yadav, R S; Agalodiya, A V; Patel, A M; Patel, S S; Patel, S I (Journal of Cereal Research, 2011)
Climatic change is likely to cause significant reduction in wheat production in India. Generally, irrigated wheat is cultivated during winter season from mid November to March in Gujarat. Therefore, temperature variation during crop growing season (i.e. Nov. to March) is an important factor to determine the productivity of wheat. Short winter with terminal heat stress is the typical climatic characteristics of the region. Results of large scale varietal trials since 1990 have been analyzed for temporal variation in wheat productivity with local checks and correlated with variation in temperature difference between maximum and minimum temperature within different growing months. Initially, this temperature difference was narrow (i.e. during 1990 to 1999) which was subsequently widened from 2000 onwards. During last few years (since 2005) this temperature difference was widest and less (between October to march) than the previous years which would be due to the recent weather abrasions. Further the analysis of wheat productivity for last twenty years was clearly indicated a positive correlation between variation in temperature difference and wheat productivity. Generally the wheat productivity was higher when the variation in temperature difference was narrow (i.e. during 1990 to 1994) and vice-versa. Further wheat productivity was increased under late sown conditions particularly 2005 onwards. Therefore, congenial wheat production conditions in changing climatic scenario should be re-assessed particularly for semi arid regions like Gujarat.